Theoretical and experimental evaluation of the influence of the length of drill rods in the SPT-T test - Peixoto, Anna Silvia Palcheco [UNESP]; Oliveira Neto, Luttgardes de [UNESP]; Antenor, Valéria Borin (My University, 2010)
The influence of soil drill rod length on the N value in the SPT-T test has been studied extensively by Mello (1971), Schmertmann & Palacios (1979), Odebrecht et al. (2002) and Cavalcante (2002). This paper presents an analysis of the Standard Penetration Test supplemented with torque measurement (SPT-T). A theoretical study of the resistance of the rod material to torsion and bending indicated that the shear stress caused by the rod self-weight represents less than 1% of that caused by the torsional moment. An experimental study with electric torquemeters attached to a horizontal rod system, as well as two field tests in the vertical direction, were also carried out to compare and substantiate the results. The purpose of these tests was to analyze changes along the length of the rod in response to successive increments at 1-meter intervals. Torque measurements were taken at each increment of the length to ascertain the accuracy of the theoretical data. The difference between the applied torque and the measured torque at the end of rod system was lower than the minimum scale of mechanical torquemeters used in practice.
Keywords: Rod length; SPT-T; Torque measurement; Torquemeter; Drillrods; Experimental evaluation; Experimental studies; Field test; N value; Rod system; Self-weight; Soil drill; Standard penetration test; T-tests; Theoretical study; Torsional moment; Vertical direction; Drill pipe; Drills; Testing; Torque meters; Torque